Medicago Sativa Defensin1 as a tumor sensitizer for improving chemotherapy: translation from anti-fungal agent to a potential anti-cancer agent - Pandurangi, Raghu; Karwa, Amol; Sagaram, Uma Shankar; Henzler-Wildman, Katherine; Shah, Dilip (Frontiers in Oncology, 2023)
MsDef1 is a 45-amino acid cysteine-rich antifungal peptide from the seed of Medicago sativa. It exhibits potent broad-spectrum antifungal activity against fungal pathogens of plants. Its mechanism of fungal growth inhibition involves binding to the cell wall localized sphingolipid glucosylceramide (GlcCer) to mediate the cytotoxic effects. Cancer cells, particularly multi-drug resistant (MDR) cancer cells overexpress GlcCer on the surface of plasma membrane. Hence, MsDef1 may have a potential to bind to GlcCer of MDR cancer cells to induce cell death. Three-dimensional structure of MsDef1 and the solution dynamics using of 15N-labeled MsDef1 nuclear magnetic resonance (NMR) spectroscopy showed that GlcCer binds MsDef1 at two specific sites on the peptide molecule. Consequently, MsDef1 permeates MDR breast cancer cells releasing ceramide and inducing apoptosis. It was also shown that MsDef1 activated dual cell death pathways ceramide and Apoptosis Stimulating Kinase ASK by disintegrating GlcCer and oxidizing thioredoxin (Trx) respectively. As a result, MsDef1 sensitizes MDR cancer cells to a chemotherapy Doxorubicin. The combination of MsDef1 and Doxorubicin induced 5 to10-fold greater apoptosis in vitro multi-drug resistant triple negative breast cancer cells MDA-MB-231R compared to either MsDef1 or Doxorubicin alone. Confocal microscopy revealed that MsDef1 facilitates a) influx of Doxorubicin in MDR cancer cells, b) preferential uptake by MDR cells but not by normal fibroblasts and breast epithelial cells (MCF-10A). Key findings of the present study include a) translation of antifungal properties of MsDef1 to antitumor properties in MDR cancer cells, b) targeting MDR cancer cells by binding of MsDef1 to GlucCer, a biomarker of MDR cancer cells and c) may find utility in improving the efficacy and reduce the toxicity of chemotherapy when used MsDef1 as an adjuvant to chemotherapy. The extension of antifungal properties of MsDef1 to cancer applications is both novel and innovative.